Association between neutrophile-to-lymphocyte ratio and risk of deep vein thrombosis in patient receiving lower extremity orthopedic surgery: A meta-analysis - I-Wen Chen; Wei-Ting Wang; Kuo-Chuan Hung (PLoS ONE, 2025)
Objective This meta-analysis aimed to quantitatively synthesize evidence on the association between the preoperative neutrophil-to-lymphocyte ratio (NLR) and the risk of deep vein thrombosis (DVT) in patients undergoing lower extremity orthopedic surgery. Methods Medline, Embase, Google Scholar, and the Cochrane Library were systematically searched for observational studies that examined the relationship between preoperative NLR and DVT risk in patients undergoing lower extremity procedures. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using random-effects models. Results Ten studies involving 5,697 patients were included in the meta-analysis. The pooled incidence of DVT across the studies was 13.8% (95% CI: 9.7%–19.2%). Elevated NLR was associated with a two-fold increase in the risk of DVT (odds ratio [OR] 2.08, 95% confidence interval [CI]: 1.39–3.12, p = 0.0004, I2 = 85%). Patients who developed DVT had a higher NLR than those who did not (mean difference: 0.93, 95% CI: 0.37 to 1.48, p =  0.001, I2 =  86%). Among the patient characteristics, male sex (OR 1.51, 95% CI: 1.12–2.03), diabetes mellitus (OR 1.60, 95% CI: 1.06–2.41), and hypertension (OR 1.43, 95% CI: 1.06–1.93) were significantly associated with increased DVT risk. Subgroup analysis based on the timing of DVT occurrence (preoperative vs. postoperative) revealed no significant difference in the association between NLR and DVT risk. Conclusion Elevated preoperative NLR was significantly associated with increased DVT risk in patients undergoing lower extremity orthopedic surgery. NLR may serve as a useful biomarker for DVT risk stratification in this population. Prospective studies are needed to validate its predictive value and evaluate NLR-guided thromboprophylaxis strategies. Trial registration PROSPERO registration number: CRD42024577952.